MYST Family Lysine Acetyltransferase Facilitates Ataxia Telangiectasia Mutated (ATM) Kinase-mediated DNA Damage Response in Toxoplasma gondii - Vonlaufen, Nathalie (American Society for Biochemistry and Molecular Biology, 2010)
The MYST family of lysine acetyltransferases (KATs) function in a wide variety of cellular operations, including gene regulation and the DNA damage response. Here we report the characterization of the second MYST family KAT in the protozoan parasite Toxoplasma gondii (TgMYST-B). Toxoplasma causes birth defects and is an opportunistic pathogen in the immunocompromised, the latter due to its ability to convert into a latent cyst (bradyzoite). We demonstrate that TgMYST-B can gain access to the parasite nucleus and acetylate histones. Overexpression of recombinant, tagged TgMYST-B reduces growth rate in vitro and confers protection from a DNA-alkylating agent. Expression of mutant TgMYST-B produced no growth defect and failed to protect against DNA damage. We demonstrate that cells overexpressing TgMYST-B have increased levels of ataxia telangiectasia mutated (ATM) kinase and phosphorylated H2AX and that TgMYST-B localizes to the ATM kinase gene. Pharmacological inhibitors of ATM kinase or KATs reverse the slow growth phenotype seen in parasites overexpressing TgMYST-B. These studies are the first to show that a MYST KAT contributes to ATM kinase gene expression, further illuminating the mechanism of how ATM kinase is up-regulated to respond to DNA damage.